BIO-EFFICACY OF NEW HERBICIDE MOLECULES FOR BROAD SPECTRUM WEED CONTROL IN TRANSPLANTED RICE (ORYZA SATIVA L.) - J. P. BHIMWAL,; P. C. PANDEY, (The Bioscan, 2014)
Comparative efficacy of different new herbicides and their dose against weeds in transplanted Kharif rice was studied at N.E. Borlaug crop research center of G.B. Pant University of Agriculture and Technology Pantnagar Uttarakhand. Nine weed control treatments viz. Flucetosulfuron 20 g ha-1 and 25 g ha-1, Penoxsulam + Cyhalofopbutyl 120 g ha-1 and 135 g ha-1, Bispyribac-sodium 35 g ha-1, Anilofos 500 g ha-1, two hand weeding weed free and weedy check were tested in a Randomized Block Design with three replications. The results revealed that the major weed flora associated with the transplanted rice during Kharif season was mainly comprised of Echinochloa spp. (32.48%), Leptochloa chinensis L. (22.49%), Commelina benghalenensis L. (15.48%), Caesulia axillaris Roxb. (15.21%), Cyperus spp. (12.63%) and other weeds (1.67%). Flucetosulfuron10 WG at 25 g ha-1 applied at 2-3 days after transplanting was found most effective to check all types of weed population and their growth. These herbicide treatments also gave the maximum grain yield (4.45 t ha-1) and straw yield (5.76 t ha-1) of rice resulting in lowest weed index (9.99%) Flucetosulfuron10 WG at 25 g ha-1 applied at 2 days after transplanting can be used safely achieve broad spectrum weed control in transplanted rice.